Electronic structure and excited state dynamics in a dicyanovinyl-substituted oligothiophene on Au(111). Issue 40 (28th September 2015) - Bogner, Lea; Yang, Zechao; Corso, Martina; Fitzner, Roland; Bäuerle, Peter; Franke, Katharina J.; Pascual, José Ignacio; Tegeder, Petra
Abstract : Using complementary experimental methods we determined the ionization potentials, affinity levels and exciton binding energies of dicyanovinyl-oligothiophene on Au(111). Abstract : Dicyanovinyl (DCV)-substituted oligothiophenes are promising donor materials in vacuum-processed small-molecule organic solar cells. Here, we studied the structural and the electronic properties of DCV-dimethyl-pentathiophene (DCV5T-Me2 ) adsorbed on Au(111) from submonolayer to multilayer coverages. Using a multi-technique experimental approach (low-temperature scanning tunneling microscopy/spectroscopy (STM/STS), atomic force microscopy (AFM), and two-photon photoemission (2PPE) spectroscopy), we determined the energetic position of several affinity levels as well as ionization potentials originating from the lowest unoccupied molecular orbitals (LUMO) and the highest occupied molecular orbitals (HOMO), evidencing a transport gap of 1.4 eV. Proof of an excitonic state was found to be a spectroscopic feature located at 0.6 eV below the LUMO affinity level. With increasing coverage photoemission from excitonic states gains importance. We were able to track the dynamics of several electronically excited states of multilayers by means of femtosecond time-resolved 2PPE. We resolved an intriguing relaxation dynamics involving four processes, ranging from sub-picosecond (ps) to several hundred ps time spans. These show a tendency to increase with increasing coverage. The present study provides important parameters such as energetic positions of transport levels as well as lifetimes of electronically excited states, which are essential for designing organic-molecule-based optoelectronic devices.